Hubungan Drug Related Problems (DRPs) Obat Antidiabetika terhadap Ketercapaian Kendali Glikemik pada Pasien Rawat Inap Diabetes Melitus Tipe 2 dengan Komplikasi Nyeri Neuropati - Anggraini Citra Ryshang Bathari; Fita Rahmawati; Ika Puspita Sari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Drug Related Problems (DRPs) associated with Type-2 Diabetes Melitus is commonly caused by multi drug prescription since Type-2 Diabetes Mellitus has comorbid dan complication diseases. Neuropathic pain has 50% prevalence of Type-2 diabetes Mellitus Complication. DRPs can cause can cause inadequate therapy that might be the risk factor leads to neuropathic pain. This study was aimed to investigate the association between drug related problems of antidiabetic medication with glicemic control of hospitalized type 2 diabetes melitus with neuropathic pain patients. Cohort-study is used in this study. 50 patients were conducted in this study that underwent Hospital treatment at Rumah Sakit Akademik Universitas Gadjah Mada during the periods of 2018-2019. This study involved 50 patients who were divided into groups that experienced DRPs by 36 patients and non DRPs by 14 patients. All of the 50 has meet the inclusions criterias. Statistical analysis was using Chi-square test 95% confidence interval (p < 0.05). A number of 38 DRPs have found consists of 26,3% need more therapy, 55,2% with wrong drug therapy, 18,4% inadequate dosing. There was an association between DRPs of antidiabetics regiments and glycemic target on Type-2 Diabetes Mellitus patients with neuropathic pain complication (p=0,005). Identification of DRPs is needed to prevent the negative effect of patient therapy outcomes.